Cadar dan Resepsi Al-Quran pada Mahasiswi IAIN Madura: Analisis pada Surah Al-Ahzab (33) Ayat 59 dan Al-Nur (24) Ayat 31 dalam Kitab Tafsir Al-Azhar - Risalatil Falihah (REVELATIA: Jurnal Ilmu Al-Qur'`an dan Tafsir, 2020)
Niqab which was known by Arabs before Islam currrently became a dress choice for other Muslimah. Use of niqab among female students at IAIN Madura increased year by year. Thus, the reason related to its use was a question of this paper. This study employed qualitative method with descriptive phenomenological approach. While the data were collected by using observation, interview and documentation technique. Some informants involved were female students whose wear niqab, lecturers and other students. Triangulation was used as data validation method. This study found that some reasons of wearing niqab among female students are the belief of self-dignity, self-guide, and the feel of self-peaceful. On the other hand, female students with niqab encountered stereotypical experiences such as judged as terrorist and being discriminated by their family and surroundings.